A new cytotoxic biflavonoid from the rhizome of Wikstroemia indica. Issue 12 (17th June 2016) - Shao, Meng; Huang, Xiao-Jun; Liu, Jun-Shan; Han, Wei-Li; Cai, Hong-Bing; Tang, Qing-Fa; Fan, Qin
Abstract : One new chalcone-flavone biflavonoid, 3′-hydroxydaphnodorin A (1 ), together with 12 known biflavonoids (2 –13 ), was isolated from the rhizome of Wikstroemia indica . Their structures were established on the basis of extensive spectroscopic methods. Eight isolated compounds1 –3, 6, 7, 9, 12 and13 were evaluated for their cytotoxic activities against cancer-derived cell lines Hep3B, HepG2 and CNE2, and1 was found to possess moderate cytotoxicity against HepG2 and CNE2 cell lines, with IC50 values of 65.5 ± 11.4 and 53.6 ± 10.1 μM, respectively. Abstract :